'Look at me! Oh Lord have mercy!': images of roller-coaster riders and the work of self-recognition. Issue 1 (2nd January 2017) - Noy, Chaim
Abstract : The omnipresence of screens in contemporary life presents an unprecedented variety of ways of displaying as well as ways of seeing, reacting to and consuming images. This paper focuses on commercial and mediatised leisure spaces in the shape of theme parks and on on-site procedures of production and display of images of roller-coaster riders. Contemporary roller-coaster machines combine speed with high-resolution photography, to supply an enmeshed, mobile-cum-visual product, and the study asks how the images are displayed – by the corporations who run the theme parks and how they are received – by the consumers. First, the material settings in which images of roller-coaster riders are produced and displayed are explored, and then the 'work' that viewers engage in when they see themselves is addressed ethnographically in detail: What discursive actions and reactions are publicly performed when consumers face their images? I conceptualise the activities of viewing, and specifically of viewing images of oneself, as 'work', a concept which I borrow from Erving Goffman (as in 'face-work') and, more recently, from Mark Andrejevic ('the work of watching'). By using qualitative and ethnographic methods, the study supplies up-close observations and analyses of the media spaces and logic in contemporary amusement parks, and the 'work' that viewers undertake when confronted with their images. This study contributes to our understanding of the proliferation of images of oneself in leisure and tourism, of the mediatisation of consumer publics, and of consumers' activities of viewing their images and reacting to them when the latter are displayed commercially on public screens.